1983
DOI: 10.1161/01.cir.68.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Action of sotalol on potential reentrant pathways and ventricular tachyarrhythmias in conscious dogs in the late postmyocardial infarction phase.

Abstract: Sotalol is a ,3-adrenergic blocker that also prolongs action potential duration and myocardial refractoriness over the short term (class III effect). Its short-term antiarrhythmic effects were compared with those of metoprolol, which has neither short-term class III nor membranestabilizing action, on reentrant ventricular arrhythmias produced by programmed stimulation in 17 conscious dogs 3 to 8 days after myocardial infarction. Ventricular arrhythmias were prevented or significantly slowed by sotalol in 11 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Before this study, Cobbe el al. (32) studied the electrophysiologic actions of sotalol in a conscious canine model of myocardial infarction. These investigators found a significant increase in ischemic zone refractoriness, the mechanism of which could not be explained.…”
Section: Methodsmentioning
confidence: 99%
“…Before this study, Cobbe el al. (32) studied the electrophysiologic actions of sotalol in a conscious canine model of myocardial infarction. These investigators found a significant increase in ischemic zone refractoriness, the mechanism of which could not be explained.…”
Section: Methodsmentioning
confidence: 99%
“…A quantitative difference thus exist be tween sotalol and metoprolol regarding the class Ill-like mode of action after long-term therapy. A qualitative difference was indicated by a previous report in which sotalol, in contrast to metoprolol, significantly prolonged ventricular refractoriness in infarcted zones compared to normal myocardium after acute administration in dogs [16]. Moreover, sotalol significantly prevented and slowed ventricular arrhythmias in ischemic myocar dium, an effect that could not be demonstrated after metoprolol treatment.…”
Section: Qrst Intervalsmentioning
confidence: 70%
“…6 The surgical technique of two-stage proximal ligation of the left anterior descending coronary7 and implantation of atrial and ventricular bipolar stimulating electrodes and subcutaneous electrocardiographic electrodes has recently been described in detail. 8 Fifteen dogs were studied with programmed stimulation over 3 to 8 days after infarction. They had been trained to stand unsedated in a sling.…”
Section: Methodsmentioning
confidence: 99%